THE CORRELATION BETWEEN VOCABULARY MASTERY AND READING COMPREHENSION : A CASE AT SMP (SLUB) SARASWATI 1 DENPASAR - Made Puspadewi; Ni Wayan Krismayani; Dewa Ayu Ari Wiryadi Joni (Academic Journal on English Studies (AJOES), 2023)
The correlation between vocabulary mastery and reading comprehension of the eighth-grade students at SMP (SLUB) Saraswati 1 Denpasar was examined in this study using a correlation research methodology. The 60 students who served as the sample were chosen using a lottery system and a random selection technique. Data were gathered using a matching cloze procedure test and a short answer test as the research tools. Prior to hypothesis testing, the data were subjected to prerequisite analysis using the Pearson product-moment correlation calculation and t-test. The data analysis's findings demonstrate that the hypothesis was accepted In other words, the findings demonstrated a significant correlation between eighth-grade SMP (SLUB) students' vocabulary mastery and reading comprehension.